2021
DOI: 10.48208/headachemed.2021.24
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric patients at a high risk of headache of ocular origin: the HAMS Score (Hyperopia, Astigmatism, Myopia, and Strabismus)

Abstract: Pediatric patients identified at increased risk for headache due to ocular refractive errors were evaluated to produce a diagnostic tool called the HAMS score that will help establish the likelihood of headache due to refractive errors.Methods Data on the ocular diagnosis and headache complaints of 726 pediatric patients of both sexes were obtained from the medical records of an ophthalmological service in Brazil (Hospital de Olhos Santa Luzia). Age, use of glasses, and ocular diagnosis were also considered to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 31 publications
0
0
0
Order By: Relevance
“…Hyperopia is the most frequent refractive error among headache patients in the present study and agrees with other studies (Akinci et al 2008;Das & Gupta 2017;Lajmi et al 2021;Gil-Gouveia & Martins 2002;Rydberg 2005;Wajuihian 2015;Vilela et al 2015;Thorud, et al 2021;Siqueira et al 2021). Hyperopia has consistently been associated with eyestrain/headache (Grosvenor 2007;Solan 1990;Rydberg 2005;Hendricks et al 2007).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Hyperopia is the most frequent refractive error among headache patients in the present study and agrees with other studies (Akinci et al 2008;Das & Gupta 2017;Lajmi et al 2021;Gil-Gouveia & Martins 2002;Rydberg 2005;Wajuihian 2015;Vilela et al 2015;Thorud, et al 2021;Siqueira et al 2021). Hyperopia has consistently been associated with eyestrain/headache (Grosvenor 2007;Solan 1990;Rydberg 2005;Hendricks et al 2007).…”
Section: Discussionsupporting
confidence: 93%
“…Anisometropia was significantly associated with temporal headaches in the present study (Table 5). Padha & Qayum 2019, Akinci et al 2008, & Siqueira et al, 2021 found significant association between headaches and anisometropia although they did not specify the headaches anatomic location. Anisometropia has been reported to cause more headaches because of the difference in error between both eyes and due to the extra effort to accommodate to a different extent between both eyes (Grosvenor 2007).…”
Section: Discussionmentioning
confidence: 99%